Competence of Quality Teachers in Improving the Quality of Education in the Digital Era - Siti Mariam; Asep Supriyadi; Asyrul Muharom; M. Nawal Hotami (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Teacher competence is a key factor in creating an effective, efficient, and meaningful learning process. A high quality teacher is not only proficient in mastering subject matter, but a professional teacher must also possess strong pedagogical, professional, personal, and social competencies. The purpose of this paper is to describe the characteristics of a quality teacher and the role of teacher in facing challenges in the digital era. The method used in this paper is a literature study with a descriptive qualitive approach. The results of the study indicate that a quality teacher is able to adaot to technology, build good communication with students and the surrounding school communit, and continuously develop themselves through ongoing training and education.